Graphene integration with nitride semiconductors for high power and high frequency electronics. Issue 4 (17th October 2016) - Giannazzo, F.; Fisichella, G.; Greco, G.; La Magna, A.; Roccaforte, F.; Pecz, B.; Yakimova, R.; Dagher, R.; Michon, A.; Cordier, Y.
Abstract : Group III nitride semiconductors (III‐N), including GaN, AlN, InN, and their alloys, are currently the materials of choice for many applications in optoelectronics (light‐emitting diodes, laser diodes), and high‐power and high‐frequency transistors. Due to its attractive electrical, optical, mechanical, and thermal properties, graphene (Gr) integration with III‐N technology has been considered in the last few years, in order to address some of the major issues which still limit the performances of GaN‐based devices. To date, most of the studies have been focused on the use of Gr as transparent conductive electrode (TCE) to improve current spreading from top electrodes and light extraction in GaN‐LEDs. This paper will review recent works evaluating the benefits of Gr integration with III‐N for high power and high frequency electronics. From the materials side, recent progresses in the growth of high quality GaN layers on Gr templates and in the deposition of Gr on III‐N substrates and templates will be presented. From the applications side, strategies to use Gr for thermal management in high‐power AlGaN/GaN transistors will be discussed. Finally, recent proposals of implementing new ultra‐high‐frequency (THz) transistors, such as the Gr base hot electron transistor (GBHET), by Gr integration with III‐N will be highlighted. Abstract : Graphene integration with group III‐nitride semiconductors can be beneficial for GaN‐based optoelectronics and high power/high frequency electronics. Furthermore, systems with interesting physical properties can arise from this materials combination. As an example, by depositing a Gr layer on top of an AlGaN/GaN heterostructure, a system is obtained where the Gr Dirac fermions are separated from the electrons at the AlGaN/GaN interface by an ultra‐thin barrier layer. This can find application in novel device concepts for ultra‐highfrequency (THz) electronics.